2020
DOI: 10.3389/fnut.2020.585306
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Promotes Macrophage-Mediated Hepatic Inflammation and Aggravates Diethylnitrosamine-Induced Hepatocarcinogenesis in Mice

Abstract: It has been reported that diet and nutrition play important roles in the occurrence and development of hepatocellular carcinoma (HCC). In this study, we investigated the potential tumor-promoting mechanisms of a high-fat diet (HFD) in mice with dietondiethylnitrosamine (DEN)-induced hepatocarcinogenesis. HFD significantly decreased the survival rate and induced severe liver dysfunction in DEN-induced mice, as indicated by increased serum glutamic-pyruvic transaminase (ALT), glutamic oxalacetic transaminase (AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
2
27
0
2
Order By: Relevance
“…Wanten et al, 2002;Khan et al, 2018;Tam et al, 2020 ↑ adhesion, apoptosis, NLRP3, NO, IL-1β, IL-6, TNF-α, NF-κB, JNK, MKK4/7, IL-10, CCL2, IFN-γ M1 polarization, CD36; ↓ phagocytosis in macrophages. Calder et al, 1990a;de Lima et al, 2006;Kim et al, 2017;Lu et al, 2017;Wang et al, 2017Wang et al, , 2021Karasawa et al, 2018;Lancaster et al, 2018;Korbecki and Bajdak-Rusinek, 2019;Fu et al, 2020;Sano et al, 2020;Youk et al, 2021 Synthetic agonist GW9508 ↑ ROS, MMP-9, COX-2, IL-8, chemotaxis in neutrophils. Hidalgo et al, 2011;Manosalva et al, 2015;Mena et al, 2016;Souza et al, 2020 ↑ PLC, PLA2, AMPK, AA; ↓ IL-6 in macrophages.…”
Section: Agonists Of the Ffa1 Receptormentioning
confidence: 99%
See 2 more Smart Citations
“…Wanten et al, 2002;Khan et al, 2018;Tam et al, 2020 ↑ adhesion, apoptosis, NLRP3, NO, IL-1β, IL-6, TNF-α, NF-κB, JNK, MKK4/7, IL-10, CCL2, IFN-γ M1 polarization, CD36; ↓ phagocytosis in macrophages. Calder et al, 1990a;de Lima et al, 2006;Kim et al, 2017;Lu et al, 2017;Wang et al, 2017Wang et al, , 2021Karasawa et al, 2018;Lancaster et al, 2018;Korbecki and Bajdak-Rusinek, 2019;Fu et al, 2020;Sano et al, 2020;Youk et al, 2021 Synthetic agonist GW9508 ↑ ROS, MMP-9, COX-2, IL-8, chemotaxis in neutrophils. Hidalgo et al, 2011;Manosalva et al, 2015;Mena et al, 2016;Souza et al, 2020 ↑ PLC, PLA2, AMPK, AA; ↓ IL-6 in macrophages.…”
Section: Agonists Of the Ffa1 Receptormentioning
confidence: 99%
“…High-fat diet (HFD) may promote hepatocarcinogenesis through an exacerbated inflammatory response that affects the liver function. In vivo experiments demonstrated that HFD affected liver function in mice, induced liver infiltration of macrophages, and increased expression of inflammatory factors, such as proliferating cell nuclear antigen (PCNA), NF-κB, cyclin D1, TNF-α, and IL-1β in the liver (Fu et al, 2020 ). In addition, to understand the link between obesity and inflammation, and its effects in pregnancy, Sano et al ( 2020 ) studied the in vivo and in vitro effects of palmitic acid in pregnant mice.…”
Section: Effects Of Lcfa On Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Dysregulation of lipids plays important roles in both the development 17 and the progression 18 of liver cancer, which is a consequence of lipids being a vast and multifarious group of complex structured biomolecules. Lipids are involved in diverse biological processes in the body from energy storage 19 and metabolism, 20 to epigenetic regulation, 21 signal transduction, 22 immunoregulation, 23 inflammation, 24 and cell-cell recognition. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Although the status of NOS expression was not showed, the results implicate altered NOS activity. On the other hand, different studies showed the pro-tumoral activity of NO-derived eNOS/iNOS in HCC growth [82,83]. González et al reported that sorafenib, a receptor tyrosine kinase, and MAPK pathway inhibitor, decreased eNOS activity and NO synthesis, attenuating proliferation and inducing apoptosis in HCC cell lines [83].…”
Section: Cell Growthmentioning
confidence: 99%